SANKSI PIDANA TERHADAP PIDANA CYBERPORN BERDASARKAN UNDANG-UNDANG NOMOR 16 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG –UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Putri Nilam Sari Cayo; Ennimerita (Justici, 2020)
ABSTRACT The spread of pornography on the internet or cyberporn is also a serious problem faced by Indonesia as a developing country that also utilizes this global technological development. In addition to imported porn sites, local porn sites have also begun to mushroom in cyberspace, such as Indonesian sites, lalatx and paradise. These sites are free and some are commercial. Regulations regarding the practice of prostitution (online prostitution) are regulated in the provisions of article 27 paragraph (1) of Law Number 16 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) Whereas the form of criminal sanctions against cyberporni through the internet is regulated in Article 45 paragraph (1) of the ITE Law